Advancements in PCB Defect Detection: An In-Depth Exploration of Image Processing Techniques - Sood, Jai; Agrawal, Manan; Pratik; Khandelwal, Richa R.; Zambani, Harish; Ghumade, Atul (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
Defect detection on Printed Circuit Boards (PCBs) is a critical process to ensure the functionality and reliability of electronic devices. Recent developments in image processing methods have demonstrated potential for increasing the accuracy of flaw detection. Nevertheless, these methods face different difficulties when it comes to fixing intricate flaws and guaranteeing reliable operation. To address these issues, a projection optical system is introduced for PCB flaw identification in this study. This research work presents a projection optical system for defect detection on printed circuit boards (PCBs). Proper defect detection ensures the production of high-quality PCBs, minimizing the risk of faulty electronics and improving overall product performance. The system uses structured light projection and image processing techniques to detect defects like scratches, cracks, and missing components. It includes an iPhone 14 Pro's camera, a light projector, and a black-covered box for positioned PCBs. The system captures and passes images through software to identify errors. The compact, portable, and user-friendly system was evaluated using test PCBs with defects. This system is valuable for improving PCB production quality and reducing manufacturing costs.